Task‐related neural mechanisms of persecutory ideation in schizophrenia and community monozygotic twin‐pairs. Issue 16 (31st July 2021) - Wisner, Krista M.; Johnson, Melissa K.; Porter, James N.; Krueger, Robert F.; MacDonald, Angus W.
Abstract: Perceptions of spiteful behavior are common, distinct from rational fear, and may undergird persecutory ideation. To test this hypothesis and investigate neural mechanisms of persecutory ideation, we employed a novel economic social decision‐making task, the Minnesota Trust Game (MTG), during neuroimaging in patients with schizophrenia ( n = 30) and community monozygotic (MZ) twins ( n = 38; 19 pairs). We examined distinct forms of mistrust, task‐related brain activation and connectivity, and investigated relationships with persecutory ideation. We tested whether co‐twin discordance on these measurements was correlated to reflect a common source of underlying variance. Across samples persecutory ideation was associated with reduced trust only during the suspiciousness condition, which assessed spite sensitivity given partners had no monetary incentive to betray. Task‐based activation contrasts for specific forms of mistrust were limited and unrelated to persecutory ideation. However, task‐based connectivity contrasts revealed a dorsal cingulate anterior insula network sensitive to suspicious mistrust, a left frontal–parietal (lF‐P) network sensitive to rational mistrust, and a ventral medial/orbital prefrontal (vmPFC/OFC) network that was sensitive to the difference between these forms of mistrust (all p < .005). Higher persecutory ideation was predicted only by reduced connectivity between the vmPFC/OFC and lF‐P networks ( p = .005), which was only observed when the intentions of the other player were relevant. Moreover, co‐twin differences in persecutory ideation predicted co‐twin differences in both spite sensitivity and in vmPFC/OFC–lF‐P connectivity. This work found that interconnectivity may be particularly important to the complex neurobiology underlying persecutory ideation, and that unique environmental variance causally linked persecutory ideation, decision‐making, and brain connectivity. Abstract : Perceptions of spiteful behavior are common, distinct from rational fear, and may undergird persecutory ideation. To test this hypothesis and investigate neural mechanisms of persecutory ideation, we employed a novel economic social decision‐making task, the Minnesota Trust Game (MTG), during neuroimaging in patients with schizophrenia ( n = 30) and community monozygotic (MZ) twins ( n = 38; 19 pairs). Behavioral and neuroimaging analyses were completed in both samples and found that interconnectivity between a left frontal–parietal (lF‐P) network and a ventral medial/orbital prefrontal (vmPFC/OFC) network may be particularly important to the complex neurobiology underlying persecutory ideation, and that unique environmental variance between twin‐pairs causally linked persecutory ideation, decision‐making, and brain connectivity.